Congenital Granular Cell Tumor of a Newborn: A Case Report - Chhanda Das; Madhumita Mukhopadhyay; Sucharita Sarkar; Bedabrata Mukhopadhyay (JCDR Research and Publications Pvt. Ltd., 2016)
Congenital Granular Cell Tumour (CGCT) is a rare benign soft tissue tumour of newborn, different from adult GCT. The tumour has a strong predilection for the maxillary alveolar ridge with a female preponderance. Here we report an unusual case of congenital granular cell epulis in the mouth of a 2 hour old female newborn. She had a round, soft, pedunculated mass measuring (2x 2x1) cm. which was causing feeding difficulty. This case was reported as congenital granular cell epulis. We are presenting this case because of its rare nature and uncommon presentation at this age.